Altered lipid homeostasis in Sertoli cells stressed by mild hyperthermia - Valles, Ana Sofia (2014)
Spermatogenesis is known to be vulnerable to temperature. Exposures of rat testis to moderate hyperthermia result in loss of germ cells with survival of Sertoli cells (SC). Because SC provide structural and metabolic support to germ cells, our aim was to test the hypothesis that these exposures affect SC functions, thus contributing to germ cell damage. In vivo, regularly repeated exposures (one of 15 min per day, once a day during 5 days) of rat testes to 43°C led to accumulation of neutral lipids. This SC-specific lipid function took 1-2 weeks after the last of these exposures to be maximal. In cultured SC, similar daily exposures for 15 min to 43°C resulted in significant increase in triacylglycerol levels and accumulation of lipid droplets. After incubations with [3H]arachidonate, the labeling of cardiolipin decreased more than that of other lipid classes. Another specifically mitochondrial lipid metabolic function, fatty acid oxidation, also declined. These lipid changes suggested that temperature affects SC mitochondrial physiology, which was confirmed by significantly increased degrees of membrane depolarization and ROS production. This concurred with reduced expression of two SC-specific proteins, transferrin, and Wilms´ Tumor 1 protein, markers of SC secretion and differentiation functions, respectively, and with an intense SC cytoskeletal perturbation, evident by loss of microtubule network (α-tubulin) and microfilament (f-actin) organization. Albeit temporary and potentially reversible, hyperthermia-induced SC structural and metabolic alterations may be long-lasting and/or extensive enough to respond for the decreased survival of the germ cells they normally foster.